The house price-vacancy curve - Oliver Lerbs; Markus Teske (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
Individual sales prices and local vacancy rates in the housing market pose a natural analogy to the wage curve, a popular concept in labor economics that describes how individual wages decrease with higher local unemployment. While housing search and matching models and housing externalities strongly suggest a stable inverse relationship, there is still a lack of convincing empirical research on the sensitivity of house sales to local vacancy variation. Based on more than 10,000 single-family home transactions from the German market, this paper confirms a robust house price-vacancy curve among individual home prices and adjacent residential vacancies. The economic size of the relationship is highly comparable across all four analyzed states: a doubling of the vacancy rate at the municipality level is associated with a 5-8% discount in quality-controlled selling prices. Despite negative price signals, local vacancy distributions tend to persist over long time horizons, leaving room for policy intervention.
Keywords: R23; R31; R58; 330; House prices; Housing vacancy; Hedonic regression; Wage curve